2006
DOI: 10.1002/jrs.1636
|View full text |Cite
|
Sign up to set email alerts
|

Direct characterization of phase behavior and compatibility in PET/HDPE polymer blends by confocal Raman mapping

Abstract: Morphology, chemical distribution and domain size in poly(ethylene terephthalate)/high-density poly(ethylene) (PET/HDPE) polymer blends of various ratios prepared with and without maleic anhydride have been analyzed with confocal Raman mapping and SEM. The ratioimage method introduced here allows us to obtain enhanced chemical images with higher contrast and reliability. Compatibility numbers (N c ) are calculated to evaluate the compatibility of the blends. The incompatible polymer blends show heterogeneous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…The dissimilarity curves during the corresponding clustering processes are shown in Figures 14.25bFi, 14.26bFi, 14.27bFi, 14.28bFi and 14.29b, respectively [34]. It is observed that there are several leaps in the curves that correspond to the number of clusters in the image data.…”
Section: Raman Imaging Of Polymersmentioning
confidence: 94%
See 3 more Smart Citations
“…The dissimilarity curves during the corresponding clustering processes are shown in Figures 14.25bFi, 14.26bFi, 14.27bFi, 14.28bFi and 14.29b, respectively [34]. It is observed that there are several leaps in the curves that correspond to the number of clusters in the image data.…”
Section: Raman Imaging Of Polymersmentioning
confidence: 94%
“…Huan et al [34] studied phase behavior and compatibility in PET/HDPE polymer blends by using confocal Raman mapping. Maleic anhydride-grafted high-density poly(ethylene) (MAH-HDPE) was prepared by melt mixing HDPE with MAH and peroxide at 220 C [51].…”
Section: Raman Imaging Of Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of special vibrational studies were reported in this reviewed JRS volume: direct characterization of the phase behavior and compatibility in polyethylene terephthalate (PET)/high-density poly(ethylene) (HDPE) polymer blends by confocal Raman mapping, 110 vibrational analysis of ethylene thiourea which provided information on the electronic distribution of nonresonant Raman excited virtual states, 111 theoretical and experimental investigations of the adsorption behavior of thiophenol on gold nanoparticles including the complete assignment of thiophenol fundamental modes, 112 correlation of the methane Raman 1 band position with fluid density and molecular level interactions, 113 Raman spectroscopic investigations of 3-(pent-1-enyl) methyl ether and four deuterium-labeled analogs enabling the correlation between specific structural features and the associated Raman bands. 114 …”
Section: Various Raman Studiesmentioning
confidence: 99%